2019
DOI: 10.1016/j.jval.2018.09.001
|View full text |Cite
|
Sign up to set email alerts
|

The Cost-Effectiveness of Financial Incentives for Viral Suppression: HPTN 065 Study

Abstract: Objective: To evaluate the cost-effectiveness of financial incentives for human immunodeficiency virus (HIV) viral suppression compared to standard of care. Study Design: Mathematical model of 2-year intervention offering financial incentives ($70 quarterly) for viral suppression (<400 copies/ml 3 ) based on the HPTN 065 clinical trial with HIV patients in the Bronx, NY and Washington, D.C. Methods: A disease progression model with HIV transmission risk equations was developed following guidelines from the Sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 58 publications
1
29
0
Order By: Relevance
“…Overall, our results are in line with studies from low‐resource settings showing that EE interventions have the potential to improve adherence outcomes among ALWHIV by mitigating the effects of poverty [16,29]. Our findings are also consistent with studies from high‐income countries reporting that financial incentives to promote ART adherence in low‐income populations are not only effective, but can also be cost‐effective in suppressing VL in HIV patients [35].…”
Section: Discussionsupporting
confidence: 90%
“…Overall, our results are in line with studies from low‐resource settings showing that EE interventions have the potential to improve adherence outcomes among ALWHIV by mitigating the effects of poverty [16,29]. Our findings are also consistent with studies from high‐income countries reporting that financial incentives to promote ART adherence in low‐income populations are not only effective, but can also be cost‐effective in suppressing VL in HIV patients [35].…”
Section: Discussionsupporting
confidence: 90%
“…the difference between studies may be due to methodological fabrication. Adamson et al, 2019 [88] Micro costing using [80] Micro costing using published data…”
Section: Unknown Perspectivementioning
confidence: 99%
“…Financial incentives have been used to promote various healthy behaviours such as medication adherence [13], reduction of substance misuse [14], or use of preventive services including voluntary medical male circumcision [15][16][17]. Recently, several clinical trials showed promising results that financial incentives could increase the uptake of HIV testing as well as linkage to care and viral load suppression but the efficacy has been varying [18][19][20][21][22][23][24][25][26]. While financial incentives may serve as once-off extrinsic motivation, providing information specific to individuals' needs can improve intrinsic motivation and empower individuals to make an informed decision to take HCT [27,28].…”
mentioning
confidence: 99%